Lessons in the Exercise of Soft Power: Oman’s Role in the Middle East (Georgetown Security Studies Review, 2016)
Keywords: Politique étrangère -- Oman -- 1970-2020

Oman as a Counter-Terrorism Model for the GCC States - Caputo, Alexandra (Terrorism Monitor, 2016)
Keywords: Politique étrangère -- Oman -- 1970-2020

La diplomatie tranquille d’Oman dans un Golfe en ébullition - En tenaille entre l’Arabie saoudite et l’Iran - Gresh, Alain (Orient XXI, 2016)
Dans un Golfe dominé par l’Arabie saoudite et où la guerre au Yémen se prolonge malgré les appels au cessez-le-feu, le sultanat d’Oman mène une politique à (...)
Keywords: Politique étrangère -- Oman -- 1970-2020

Medio Oriente. L'Oman neutrale, un «lusso» da tutelare - Zoja, Federica (www.avvenire.it, 2016)
​​Il nodo successione nella Svizzera del Medio Oriente. Il pericolo viene da fronti interni ed esterni e la posiizione degli alleati occidentali è ambigua.
Keywords: Politique étrangère -- Oman -- 1970-2020

Oman Can Help Trump Navigate the Middle East - Cafiero, Giorgio (LobeLog, 2016)
by Giorgio Cafiero Immediately after Donald Trump’s victory, Sultan Qaboos sent the New York mogul a congratulatory cable to wish him “success in leading the U.S. people towards further progress an…
Keywords: Politique étrangère -- Oman -- 1970-2020

How Oman is helping Obama shut down Guantanamo Bay - Cafiero, Giorgio (Al-Monitor, 2016)
As the primary destination for transferred Guantanamo Bay prisoners, Oman solidifies its role as a diplomatic back channel for the United States.
Keywords: Politique étrangère -- Oman -- 1970-2020

The sultanate of Oman: true Arabia and zero terrorism - Maksimovic, Sandra (SARAH MAX RESEARCH, 2016)
WHY IS THIS ABSOLUTE MONARCHY, BASED ON  IBADISM   A GOOD EXAMPLE FOR ALL MUSLIM COUNTRIES TO FOLLOW ? This exotic country, located on Arabic Peninsula with the 5000 years old history and the best …
Keywords: Politique étrangère -- Oman -- 1970-2020

Oman : une autre géopolitique dans le monde arabe - Rodríguez, Sonia; Abidi, Hasni (Iris, 2016)
Le Sultanat d’Oman est un pays du Moyen-Orient souvent méconnu du grand public. Fort d’une influence douce dans les relations internationales, ses choix politiques sont orientés par la diplomatie discrète et par une tradition de tolérance, ce qui le positionne comme acteur géostratégique central de la région. Depuis la prise...
Keywords: Politique étrangère -- Oman -- 1970-2020